Association Between Fatty Liver and Cirrhosis, Hepatocellular Carcinoma, and Hepatitis B Surface Antigen Seroclearance in Chronic Hepatitis B. (29th November 2020) - Li, Jie; Yang, Hwai-I; Yeh, Ming-Lun; Le, Michael H; Le, An K; Yeo, Yee Hui; Dai, Chia-Yen; Barnett, Scott; Zhang, Jian Q; Huang, Jee-Fu; Trinh, Huy N; Wong, Christopher; et al.
Abstract: Background: Chronic hepatitis B (CHB) and fatty liver (FL) are common, natural history data on concurrent FL and CHB (FL-CHB) are limited. This study aimed to evaluate the effect of FL on cirrhosis, hepatocellular carcinoma (HCC), and hepatitis B surface antigen (HBsAg) seroclearance incidence in CHB patients. Methods: In a retrospective cohort study of 6786 adult CHB patients, we used propensity score matching (PSM) to balance the FL-CHB and non-FL CHB groups. Kaplan-Meier methods were used to compare cumulative cirrhosis, HCC, and HBsAg seroclearance rates between subgroups. Results: Before PSM, compared to non-FL CHB, FL-CHB patients had lower 10-year cumulative rates of cirrhosis, HCC, and a higher HBsAg seroclearance rate. Similar results were found in the matched FL-CHB and non-FL CHB patients, as well as in the antiviral-treated PSM cohort. Cox proportional hazards model indicated FL to remain significantly and strongly associated with lower risk of cirrhosis and HCC (hazard ratio [HR], 0.19 [95% confidence interval CI, .12–.33], P < .001 and HR, 0.21 [95% CI, .09–.51], P = .001, respectively) in antiviral-treated patients but not in untreated patients. Conclusions: FL was significantly associated with lower cirrhosis and HCC risk and higher HBsAg seroclearance. Further studies are needed to confirm our funding and investigate the mechanisms underlying the impact of FL on CHB. Abstract : In this retrospective cohort study of 6786 adult patients with chronic hepatitis B (CHB), we observed a consistently lower incidence of cirrhosis, hepatocellular carcinoma, and higher incidence of hepatitis B surface antigen seroclearance in CHB patients' concurrent fatty liver (FL), compared to non-FL CHB patients.